Sodium-Selective Channelrhodopsins - Ariel Coli; Shiqiang Gao; Lars Kaestner (Cells)
Channelrhodopsins (ChRs) are light-gated ion channels originally discovered in algae and are commonly used in neuroscience for controlling the electrical activity of neurons with high precision. Initially-discovered ChRs were non-selective cation channels, allowing the flow of multiple ions, such as Na+, K+, H+, and Ca2+, leading to membrane depolarization and triggering action potentials in neurons. As the field of optogenetics has evolved, ChRs with more specific ion selectivity were discovered or engineered, offering more precise optogenetic manipulation. This review highlights the natural occurrence and engineered variants of sodium-selective channelrhodopsins (NaChRs), emphasizing their importance in optogenetic applications. These tools offer enhanced specificity in Na+ ion conduction, reducing unwanted effects from other ions, and generating strong depolarizing currents. Some of the NaChRs showed nearly no desensitization upon light illumination. These characteristics make them particularly useful for experiments requiring robust depolarization or direct Na+ ion manipulation. The review further discusses the molecular structure of these channels, recent advances in their development, and potential applications, including a proposed drug delivery system using NaChR-expressing red blood cells that could be triggered to release therapeutic agents upon light activation. This review concludes with a forward-looking perspective on expanding the use of NaChRs in both basic research and clinical settings.